Film Bulk Acoustic Resonators for Nitrogen Monoxide Detection at 250 °C - José Manuel Carmona-Cejas; Teona Mirea; Ricardo Hervás; Jimena Olivares; Marta Clement (Proceedings)
Exposure to hazardous gases like NOx can have a negative impact on our health. High-performance sensors are needed to control high levels of these contaminants, which, in most cases, are generated by automotive exhaust or industrial factories. In this work we demonstrate NO detection below the ppm level by employing an AlScN-based FBAR covered with a sputtered WO3 active layer. FBARs are potential candidates as they have also proved operation and stability in harsh environments as well as temperature and humidity discrimination with a single sensor.